OMEGA – OSIRIS Mapping of Emission-line Galaxies in A901/2: II. Environmental influence on integrated star formation properties and AGN activity - Rodríguez del Pino, Bruno; Aragón-Salamanca, Alfonso; Chies-Santos, Ana L.; Weinzirl, Tim; Bamford, Steven P.; Gray, Meghan E.; Böhm, Asmus; Wolf, Christian; Maltby, David T. (Oxford University Press, 2017)
We present a study of the star formation and AGN activity for galaxies in CP 15051 the Abell 901/2 multicluster system at z ∼ 0.167 as part of the OSIRIS Mapping of Emission-line Galaxies in A901/2 (OMEGA) survey. Using Tuneable Filter data obtained with the OSIRIS instrument at the Gran Telescopio Canarias, we produce spectra covering the Hα and [NII] spectral lines for more than 400 galaxies. Using optical emission-line diagnostics, we identify a significant number of galaxies hosting AGN, which tend to have high masses and a broad range of morphologies. Moreover, within the environmental densities probed by our study, we find no environmental dependence on the fraction of galaxies hosting AGN. The analysis of the integrated Hα emission shows that the specific star formation rates of a majority of the cluster galaxies are below the field values for a given stellar mass. We interpret this result as evidence for a slow decrease in the star formation activity of star-forming galaxies as they fall into higher density regions, contrary to some previous studies that suggested a rapid truncation of star formation. We find that most of the intermediate- and high-mass spiral galaxies go through a phase in which their star formation is suppressed but still retain significant star formation activity. During this phase, these galaxies tend to retain their spiral morphology while their colours become redder. The presence of this type of galaxies in high-density regions indicates that the physical mechanism responsible for suppressing star formation affects mainly the gas component of the galaxies, suggesting that ram-pressure stripping or starvation is potentially responsible.